Flight Price Prediction Using Machine Learning Techniques - Panda, BS; Varma, B Phanendra; B Chandini, B Chandini; R. Bhoomika (International Journal of Computer Sciences and Engineering, 2022)
This article will examine the issue of foreseeing air passages. To do this, a great deal of things has been distinguished, and you believe that the qualities of a typical airplane will influence the cost of aircraft tickets. Highlights are utilized in eight current AI strategies, used to foresee airplane costs, and model execution is thought about. As well as cautiously anticipating each model, this paper cautiously inspects the data used to distinguish carrier tickets.